Peranan Rekrutmen DPRK terhadap Independensi Komisi Independen Pemilihan Kabupaten Pidie Periode 2018-2023 - Nur Marisa; Subhilhar Subhilhar; Heri Kusmanto (PERSPEKTIF, 2022)
This study discusses the role of DPRK recruitment on the independence of the Pidie Regency Election Independent Commission for the 2018-2023 period. The problem is focused on the anomaly in the recruitment process for election organizers in Aceh. The theory used is the theory of independence and the theory of political recruitment model Rush and Althof (1997). This study uses a qualitative method. Data sources consist of primary and secondary data. Primary data was obtained from in-depth interviews with a number of informants, while secondary data was obtained from literature review and related documents. Research informants consisted of parties involved in the recruitment of Pidie Regency KIP Members for the 2018-2023 period, both political parties and independent teams as well as the community. The results of the study show that the dynamics of political interests in the selection stages of KIP Pidie occur at the stages of agency, criteria, control, and demands. The formation of an agency, namely an independent team as a selection committee in the recruitment of KIP Pidie members for the 2013-2018 period was formed without considering expertise and coming from people with unclear backgrounds. At the criteria stage, there is no standard standard for the main criteria in determining graduation in the selection of organizers. At the control stage, recruitment is done openly but with minimal public supervision and is under the full control of the Pidie DPRK. The party's strong control over the recruitment process coupled with the lack of control outside the local parliament has put the independence of the organizers into doubt.